Analytical validation of an ultraviolet–visible procedure for determining vitamin D3 in vitamin D3-loaded microparticles and toxigenetic studies for incorporation into food - Silva, Tamires Barlati Vieira da (2018)
Vitamin D is a water-insoluble compound presented in two main forms (D2 and D3), susceptible to environmental conditions. Microencapsulation is an alternative to supplements and preserve vitamin D properties in foods. Entrapment efficiency (EE) is the main property to evaluate the encapsulation effectiveness and therefore it is of interest the study of analytical methods for the identification and quantification of this compound within the particle. This paper describes a low cost UV–Vis methodology validation to the identification and quantification of vitamin D3 in microparticles produced by hot homogenization. The method was validated following the International Conference on Harmonization (ICH) guidelines. To guarantee safe application in foodstuff, microparticles toxigenicity was evaluated with Allium cepa L. in vivo model, showing no cytotoxic nor genotoxic potential. High entrapment efficiency was obtained, the results also demonstrated that the concentration of vitamin D3 in microparticles can be safely accessed by the validated method.